Impact of Prior Season Influenza Vaccination on Seasonal Influenza Vaccine Effectiveness: An Analysis over Four Consecutive Seasons from the Serious Outcomes Surveillance (SOS) Network of the Canadian Immunization Research Network (CIRN). (4th October 2017) - Nichols, Michaela; Ye, Lingyun; Andrew, Melissa K; Hatchette, Todd; Ambrose, Ardith; Boivin, Guy; Bowie, William R; Santos, Gael Dos; Elsherif, May; Green, Karen; Haguinet, Francois; Katz, Kevin; et al.
Abstract: Background: Recent controversy has arisen from observational studies suggesting a potential negative association between prior influenza vaccination and subsequent influenza vaccine effectiveness (VE). As immunologic theories suggest this impact could vary by season/strain, we investigated this association over 4 influenza seasons in Canada. Methods: The CIRN SOS Network prospectively enrolled laboratory-confirmed influenza cases and influenza-negative controls admitted to participating hospitals. Using a test-negative control design, matched conditional logistic regression modeling stratifying participants into 4 groups (not vaccinated current or prior season [referent], vaccinated prior season only, vaccinated current season only, and vaccinated both current and prior season) was used to calculate odds ratios (OR) to estimate the effect of vaccination status on influenza-related hospitalization (VE= 1-OR x100). We assessed VE overall and stratified by strain (A/H3N2, A/H1N1, and influenza B) for 4 influenza seasons in Canada: 2011/2012–2014/2015. Results: Although impact of prior vaccination varied, the largest strain-specific impacts were observed in the H3N2 dominant seasons 2012/2013 and 2014/2015, seasons where the H3N2 vaccine component was matched, and mismatched, respectively, to the circulating strain. In 12/13, adjusted VE against influenza H3N2 hospitalization was 58.6% (95% Confidence Interval [CI]: 32.5–74.7%) for patients vaccinated in current season only, relative to 30.9% (10.8–46.5%) among those vaccinated in both prior and current season; VE against influenza B hospitalization in 12/13 was 83.2% (18.9–96.5%) in current season only vaccinees and 54.1% (-6.0–80.2%) in both seasons vaccinees. In 14/15, H3N2 VE was 35.3% (-32.6–68.5%) in current season only vaccinees and -8.3% (-56.7–25.1%) in both seasons vaccinees. Conclusion: While our findings support a possible negative association between prior influenza vaccination and subsequent season VE against some strains in certain seasons, non-statistically significant reductions in VE were observed. Future prospective studies, using varying methodology to examine this association and to explore contributing biological/immunological mechanisms, are critical to inform immunization policy. Disclosures: M. K. Andrew, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant; Sanofi-Pasteur: Grant Investigator, Research grant; T. Hatchette, GSK: Grant Investigator, Grant recipient; Pfizer: Grant Investigator, Grant recipient; Abbvie: Speaker for a talk on biologics and risk of TB reactivation, Speaker honorarium; G. Dos Santos, GSK: Employee, Salary; Business and Decision Life Sciences (Contractor for GSK Vaccines): Independent Contractor, Salary; M. Elsherif, Canadian Institutes of Health Research: Investigator, Research grant; Public Health Agency of Canada: Investigator, Research grant; GSK: Investigator, Research grant; F. Haguinet, GSK: Employee, Salary; J. Mcelhaney, GSK: Scientific Advisor, Honorarium to institution; sanofi pasteur: Scientific Advisor, Honorarium to institution; A. Mcgeer, Hoffman La Roche: Investigator, Research grant; GSK: Investigator, Research grant; sanofi pasteur: Investigator, Research grant; J. Powis, Merck: Grant Investigator, Research grant; GSK: Grant Investigator, Research grant; Roche: Grant Investigator, Research grant; Synthetic Biologicals: Investigator, Research grant; M. Semret, GSK: Investigator, Research grant; Pfizer: Investigator, Research grant; R. Sharma, GSK: Employee and Shareholder, Salary; V. Shinde, Novavax: Employee, Salary; GSK: Shareholder, Stocks; GSK: Employee, Salary; S. Trottier, Canadian Institutes of Health Research: Investigator, Research grant; S. McNeil, GSK: Contract Clinical Trials and Grant Investigator, Research grant; Merck: Contract Clinical Trials and Speaker's Bureau, Speaker honorarium; Novartis: Contract Clinical Trials, No personal renumeration; sanofi pasteur: Contract Clinical Trials, No personal renumeration